Grieks-Romeinse apokaliptiek en die Christelike kerugma - Boshoff, H.J. (HTS teologiese studies, 2005)
Greco-Roman apocalypticism and the Christian kerygmaThis study aims to show that the idea of the kingdom of God can be viewed as an apocalyptic alternative to the Pax Romana. The apocalyptic thinking of the Roman Empire had a profound influence on the kerygma of Jesus and his followers. Therefore, the kingdom of God came to replace the Pax Romana and this replacement took form in the kerygma of Jesus Christ. It is the view expressed in this study that the Christian view of the kingdom as a present-day reality derived from the apocalyptic idea of the Roman Empire as an existing utopia.